Simulating Forward-Looking Models - Dag Kolsrud (Norges Bank, 2001)
The solutions of a macroeconometricmodel with expectations of future-dated variables has to be approximated by numerical simulations. A brief review of deterministic and stochastic dynamic simulations of a backward-looking model is followed by a conceptual presentation of methods for dynamic simulations of a forward-looking (rational expectations) model. Detailed numerical methods for solving the models are beyond the scope of this note.
hdl:11250/2498712
Keywords: C15; C30; C63; 330; forward-looking models; rational expectations; simultaneous equation systems; stochastic simulation